Guide to choosing internet of things protocols - Sakina Elhadi; Loubna Chhiba; Nawal Sael; Abdelaziz Marzak (Institute of Advanced Engineering and Science, 2022)
The internet of things (IoT) is a global infrastructure for the information society, enabling advanced services by interconnecting objects (physical or virtual) through existing or evolving interoperable information and communication technologies. Among the main keys to the IoT is the widespread adoption of clearly defined protocols. The implementation of its applications requires protocols capable of effectively managing these conditions, namely network protocols and applications. Considering the importance of using protocols in IoT applications, many protocols have been developed and used by various organizations according to their needs. However, choosing an adaptable, standard, and efficient protocol is a difficult decision, for all organizations and researchers. This difficulty, due to the complex nature of the IoT system and its requirements. Consequently, we propose a model for the use of IoT protocols based on criteria and metrics that will evolve the protocols. we call these models by the model of good practice of protocols of the Internet of things. Then, we implement these models in the form of a tool for choosing IoT (Networks and application) protocols. This study will allow researchers and developers to choose the appropriate protocols for an IoT application by allowing the result before the realization of the application.